PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP KEMAMPUAN BERFIKIR KREATIF MATEMATIKA SISWA DI SMP NEGERI 11 PADANGSIDIMPUAN - Haritsah Hammamah Harahap; Agus Makmur Panjaitan (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2019)
This research is a research experiment, with the entire population of students of class VIII SMP Negeri 11 Padangsidimpuan which consists of 3 classes. Sampling in this research is done by using the technique of cluster sample, which of the engineering cluster sample. Data analysis techniques include test normality, test its homogeneity and test hypotheses. Hypothesis testing is carried out by two roads at anava extent confidence α = 0.05. The results of the analysis on two path with cell anava not same retrieved F_a = F_tabel =18,51 with 1,079. Furthermore the research results obtained from the average of 78.00 experiment class while the average classroom control now and results at 71.96 class experiment 4.15 while 3.48 control class. The descriptive data analysis used in the observation activities of the students and the students answer patterns. Observation results acquired the levels of activity of the students in the class of experiment of 75.81% with good qualifications while at 67.81% control classes with qualified enough. As for the pattern of experimental class students answer better than the class of the control. Based on the research results, it is recommended to apply the cooperative learning model type of the talking stick. Keywords: the talking stick, creative thinking, research experiment